2019
DOI: 10.1186/s12889-019-6423-z
|View full text |Cite
|
Sign up to set email alerts
|

Health and social impacts of open defecation on women: a systematic review

Abstract: BackgroundThe significance of sanitation to safeguard human health is irrefutable and has important public health dimensions. Access to sanitation has been essential for human dignity, health and well-being. Despite 15 years of conjunctive efforts under the global action plans like Millennium Development Goals (MDGs), 2.3 billion people have no access to improved sanitation facilities (flush latrine or pit latrine) and nearly 892 million of the total world’s population is still practicing open defecation.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 39 publications
5
92
0
Order By: Relevance
“…Caruso et al [28] have investigated women's security issues in relation to sanitation and open defecation. Saleem et al [6] reported that there is an increased risk to women and girls due to the practice of open defecation. Access to safe toilets has a prominent role in defending women's safety and self-esteem.…”
Section: Impact Of Open Defecation On Sdgmentioning
confidence: 99%
See 2 more Smart Citations
“…Caruso et al [28] have investigated women's security issues in relation to sanitation and open defecation. Saleem et al [6] reported that there is an increased risk to women and girls due to the practice of open defecation. Access to safe toilets has a prominent role in defending women's safety and self-esteem.…”
Section: Impact Of Open Defecation On Sdgmentioning
confidence: 99%
“…Accessibility to basic sanitation and hygiene does have a major impact on public health, child mortality, education, economic development, and ecosystem quality [5]. Women and girls are not only susceptible to the health consequences of poor sanitation, but also to the danger of physical assaults and wild animal encounters [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Open defecation is an issue that can affect everyone but women are often at more risk of experiencing violence and multiple health vulnerabilities and women with poor sanitation facilities are more susceptible to hookworm infestation resulting in maternal anemia, which in turn is directly associated to adverse pregnancy outcomes. 4 Further evidence by media analysis and reporting show that adolescent girls and young women going for open air defecation have to bear extreme hardships and vulnerabilities. They are subjected to eve teasing and other forms of sexual exploitation besides having to cope with the vagaries of weather and other hazards on a daily basis.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of open defecation has become one of the factors that drive citizens to be lazy to use public toilets (Chitra Dewi, 2019). ODF remains the leading cause of water pollution, the spread of infectious diseases that immediately have an impact on public health (Saleem, Burdett, & Heaslip, 2019).…”
Section: Introductionmentioning
confidence: 99%